Linking Ethical Leadership and Organizational Social Capital Towards Enhancing Organizational Performance in the Somali Public Sector - Mohamed Abdi, Ahmed Nor; Hashi, Mohamed Bile (2023)
Public administration scholars have continued to be interested in organizational performance and have attempted to understand its influencing factors. Public sector organizational performance is vital because it helps the sector accomplish better with limited resources. In the private sector, there is conclusive evidence of organizational performance and the factors that influence it. However, the issue is largely unknown and under-researched in the public sector, particularly in the Somali context. Thus, grounded in social capital and social learning theories, the study aims to unveil the impact of ethical leadership on public sector organizational performance in Somalia via the underlying mechanism of organizational social capital. Data were gathered from 343 public servants in two Somali regional administrations (the Banadir and Jubaland). SmartPLS 4 software was used to analyze the data. The results showed that the ethical leadership of public-sector organizations positively and significantly impacts both public-sector organizational performance and organizational social capital. Moreover, the findings showed that social capital partially mediates the association between ethical leadership and public-sector organizational performance. The results of this study have important implications for policymakers and public sector leaders in Somalia. The present study is the first to model the mediating effect of public-sector organizational social capital in the association between ethical leadership and public sector organizational performance in Somalia.